A stable graphite electrode in superconcentrated LiTFSI-DME/DOL electrolyte and its application in lithium-sulfur full battery. (November 2017) - Zeng, Pan; Han, Yamiao; Duan, Xiaobo; Jia, Guichong; Huang, Liwu; Chen, Yungui
Graphical abstract: In superconcentrated ether-based solutions, the formed SEI film inhibits electrolyte decomposition and graphite exfoliation caused by co-intercalation of solvents. Thus, reversible lithium intercalation and de-intercalation at a graphite electrode has been realized. Highlights: Prelithiated graphite anodes are coupled with sulfur composite cathodes to form a Li–S full cell in superconcentrated LiTFSI-DME/DO electrolyte. The introduced superconcentrated ether-based electrolyte permits reversible lithium intercalation and de-intercalation at a graphite electrode. The assembled Li–S full battery exhibits better cycle performance and coulombic efficiencies. Abstract: Herein, prelithiated graphite anodes are coupled with sulfur composite cathodes to form a Li–S full cell in superconcentrated ether electrolyte. This novel system is effective in avoiding sever corrosion of Li-metal anode and significantly improving the safety of present Li–S cell, owing to the replacement of Li-metal anode with graphite. The introduced superconcentrated ether electrolyte has a unique networking structure of Li cations and TFSI anions with Li + -solvating DME/DOL solvents, which is conducive to form a stable TFSI-derived surface film on the graphite electrode. The stable and dense TFSI-derived film inhibits further electrolyte decomposition and graphite exfoliation caused by co-intercalation of solvents, allowing reversible lithium intercalation and de-intercalation at a graphite electrode. Besides, the severe polysulfides shuttle is also suppressed by the concentrated ether-based solutions. Consequently, the assembled graphite-sulfur full battery retains outstanding capacity of 686 mAh g −1 sulfur at 0.1C rate after 105 cycles, along with high Coulombic efficiency.